Consumer Perception about Selected Aspects of Global and Local Brands - Singh, Dr. Trilok Pratap (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to examine the relationship between consumer brand equity (CBE). This work examines the gaps between global and local brands in the Indian market. Attitudes towards items around the world and the casual clothing brand of the Indian market are being investigated. Brand equity, consisting of brand identity, impact on the perception of consumer products regardless of age (people, inclination to local brands, personal experience, costs, advertising, sponsorships and endorsements) are recognized. A total of 255 students took part in the survey. This research shows that Indian consumers perceive global and local brands differently based on brand meaning.